Endobronchial Valves for the Treatment of Bronchopleural Fistula and Pneumothorax Caused by Pulmonary Cryptococcosis in an AIDS Patient - Wen, Ying; Liang, Chao-nan; Zhou, Ying; Ma, Hai-feng; Hou, Gang (Frontiers in Medicine, 2020)
Cryptococcal disease is an opportunistic infection that occurs primarily among people with advanced HIV disease and is an important cause of morbidity and mortality. Spontaneous pneumothorax (SP) is rare in AIDS patients with pulmonary cryptococcosis (PC), but when it occurs, rapid and effective treatment is crucial to the prognosis. Here, we report a case of spontaneous pneumothorax during treatment of cryptococcal disease in a patient with AIDS. The pneumothorax remained despite chest tube drainage and evolved into a bronchopleural fistula that was confirmed by the Chartis system. The pneumothorax was significantly resolved following the placement of 2 endobronchial valves (EBVs). The patient tolerated the procedure very well and the pneumothorax gradually resolved. When immunocompromised hosts suffer from refractory pneumothorax or prolonged air leaks, endobronchial valve implantation could be a minimally invasive, optimal treatment.